Leakage, welfare, and cost-effectiveness of carbon policy - Kathy Baylis; Don Fullerton; Dan Karney (Center for Economic Studies and ifo Institute (CESifo), 2013)
We extend the model of Fullerton, Karney, and Baylis (2012 working paper) to explore cost-effectiveness of unilateral climate policy in the presence of leakage. We ignore the welfare gain from reducing greenhouse gas emissions and focus on the welfare cost of the emissions tax or permit scheme. Whereas that prior paper solves for changes in emissions quantities and finds that leakage maybe negative, we show here that all cases with negative leakage in that model are cases where a unilateral carbon tax results in a welfare loss. With positive leakage, however, a unilateral policy can improve welfare.
Keywords: H23; Q28; Q48; Q58; 330; trade and environment; pollution havens; unilateral climate policy; Klimaschutz; Soziale Kosten; Außenwirtschaft; Ökosteuer; Substitutionseffekt; Auslandsverlagerung; Theorie